2020
DOI: 10.14569/ijacsa.2020.0110824
|View full text |Cite
|
Sign up to set email alerts
|

The TPOA Telecentre: A Community Sustainable Telecentre Architecture

Abstract: This paper presented the telecentre implementation for the Orang Asli villages in remote rural areas under the Telecentre Program for Orang Asli (TPOA). TPOA telecentre architecture aims to assist the achievement of a rural community sustainable telecentre through innovation and strategic adoption of ICT technology. Lessons learned from our past telecentre experience have outlined various challenges in the technical aspects of the telecentre implementation and operation.The TPOA telecentre ICT architecture has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…In fact, to further mitigate the situations, the devises are designed to be self‐automated, their contents are synchronized virtually; and if the telecentre caretakers encounter any problems they can be remotely assisted in solving the issues. Four devices were innovated for the purpose: the quick restart mechanism, the self‐management portal guide, the self‐training platform and the remote access management devise (for details of these devises, see Tan, Bala, Lau, & Wong, 2020).…”
Section: Terrain Constraints and The Creation Of Remote Virtual Management Schemementioning
confidence: 99%
“…In fact, to further mitigate the situations, the devises are designed to be self‐automated, their contents are synchronized virtually; and if the telecentre caretakers encounter any problems they can be remotely assisted in solving the issues. Four devices were innovated for the purpose: the quick restart mechanism, the self‐management portal guide, the self‐training platform and the remote access management devise (for details of these devises, see Tan, Bala, Lau, & Wong, 2020).…”
Section: Terrain Constraints and The Creation Of Remote Virtual Management Schemementioning
confidence: 99%
“…Lwoga and Chigona (2018) reported that in Tanzania, power outages were among the barriers that affected telecentres in the provision of information services to the people. Frequent power outages could easily affect the primary purpose of the telecentre as most of its services such as photocopy, printing, internet services and others are power dependent (Tan et al, 2020).…”
Section: Limited Space Within Telecentresmentioning
confidence: 99%
“…Recently, Telecentre Programme for Orang Asli (TPOA) in Sarawak, West Malaysia is a community-university based initiative in partnership with the Department of Orang Asli Development (JAKOA) is committed to develop community telecentre as a platform to enhance quality of life. TPOA also facing problems with internet connectivity and accessibility (UNIMAS, 2019;Chong et al;2020).…”
Section: The Telecentre Conceptmentioning
confidence: 99%
“…Sustainability of a Telecentre is the "Capacity to generate enough revenue from ICT enabled services to ensure continues existence in the community, fulfilling the socio-economic well-being of the society" (Niranjan M, 2009;Chong et al;2020). The problem related to this research is policy failure at the institutional capacity.…”
Section: Sustainability Concept Of Telecentresmentioning
confidence: 99%